Analisis Pemahaman Penggunaan Media Sosial Tiktok Dalam Cara Komunikasi - Yusuf, Dhea Fadillah; Fahrunissa, Abhinaya Rizki; Habibie Hrp, M. Rizki; Putri, Adelia; Gea, Adela Frianjani; Lubis, Parlindungan; Harahap, Nursapia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes user comprehension of TikTok as an interactive communication tool among students at the State Islamic University of North Sumatra (UINSU). Using a qualitative phenomenological approach, the research involved eight participants through in-depth interviews. The findings indicate that TikTok serves as a medium for expanding social networks, sharing creative content, and enhancing digital literacy. However, it also faces challenges such as the spread of fake news and cyberbullying. This study recommends developing digital literacy programs and content oversight to foster a healthier digital ecosystem.